Pulsed Radiation Therapy to Improve Systemic Control of Metastatic Cancer - He, Kewen; Barsoumian, Hampartsoum B.; Sezen, Duygu; Puebla-Osorio, Nahum; Hsu, Ethan Y.; Verma, Vivek; Abana, Chike O.; Chen, Dawei; Patel, Roshal R.; Gu, Meidi; Cortez, Maria Angelica; Welsh, James W. (Frontiers in Oncology, 2021)
Radiation therapy (RT) is emerging as an interventional modality in the cancer-immunity cycle, augmenting the activation of an adaptive immune response against tumors. RT, particularly in combination with immunotherapy, can enhance immune memory effects and shape the tumor-directed T-cell populations. However, a single cycle of RT delivered to a limited number of polymetastatic lesions is rarely sufficient to achieve systemic control. We hypothesize that several rounds of RT, akin to several rounds of immunotherapeutic drugs, is likely to provide greater clinical benefit to patients with metastatic disease. We propose that the repeated exposure to tumor antigens released by “pulsed-RT” (i.e., treating 2-4 tumor lesions with 3 irradiation cycles given one month apart) may amplify the adaptive immune response by expanding the tumor-specific T-cell receptor repertoire, the production of high-affinity tumor antibodies, and the generation of memory lymphocytes and thereby improve immune control of systemic disease.